Competitiveness and Export Similarity of Indonesia’s Coconut Oil - Anisa Nurina Aulia; Nur Chasanah; Agus Subhan Prasetyo; Ara Nugrahayu Nalawati (AGRIBEST, 2020)
Coconut oil is one of the vegetable oils that became potential export product in Indonesia. Philippines, Indonesia, and Malaysia are three of the biggest exporters of coconut oil in ASEAN, by knowing their position in the Internastional trade of Coconut Oil it become an evauation for the sustainability of the Indonesia’s coconut oil trade.,The aims of this research are knowing the position of Coconut Oil (Crude Coconut Oil with HS Code 151311 and Its derivative with HS code 151319) compared to the competitors during 2001 to 2017 by using Revealed Comparative Advantage (RCA), Acceleration Ratio (AR), Trade Specialization Index (ISP) and Export Similarity Index (ESI) for adding information about the similarity of the export structure of coconut oil from Indonesia, Philippines, and Malaysia to the world market. The results of the research show that Indonesia has high competitiveness, and has the highest acceleration in the growth of Crude Coconut Oil’s exports (HS Code 151311) compared to the Philippines and Malaysia. Meanwhile, Indonesia and Philipines have a higher similarity market of coconut oil than Indonesia and Malaysia. Indonesia should increase the capacity industries for derivative of crude coconut oil (HS code 151319) so it could increase volume and value export because it has a higher benefit than crude coconut oil.